Game Theory Analysis of Indihome and Biznet in the Salatiga Internet Market - Christanto, Henoch Juli (Universitas Bina Darma, 2024)
With the rapid expansion of internet usage in Indonesia, comprehending the competition within the internet service provider sector has become imperative. This study investigates the competitive dynamics between Indihome and Biznet in the Salatiga internet market, examining various strategic dimensions such as pricing strategies, network quality, promotions, payment models, customer service, accessibility, product portfolios, and data security. Employing game theory methodology, the research discerns optimal strategies for each provider, utilizing maximin and minimax strategies to minimize potential losses and maximize potential gains. Validity and reliability testing ensures the integrity of the analysis, confirming the validity and reliability of all variables. Results reveal that Indihome employs strategy X5 (Customer Service) to attain a maximum profit of 36, while Biznet adopts the same Y5 strategy to minimize a loss of 36. This study provides valuable insights for both service providers to adeptly navigate the competitive landscape.